2002
DOI: 10.1182/blood.v99.8.2786
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic cells expressing the peripheral cannabinoid receptor migrate in response to the endocannabinoid 2-arachidonoylglycerol

Abstract: Cb2 is a novel protooncogene encoding the peripheral cannabinoid receptor. Previous studies demonstrated that 2 distinct noncoding first exons exist: exon-1A and exon-1B, which both splice to proteincoding exon-2. We demonstrate that in retrovirally induced murine myeloid leukemia cells with proviral insertion in Cb2, exon-1B/exon-2 Cb2 messenger RNA levels have been increased, resulting in high receptor numbers. In myeloid leukemia cells without virus insertion in this locus, low levels of only exon-1A/exon-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(31 citation statements)
references
References 63 publications
2
29
0
Order By: Relevance
“…We observed induction of Sca-1 expression, as well as induction of PECAM-1 and Flk-1 expression during ES cell differentiation (Fig. 1C), which is in agreement with other published reports [30].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…We observed induction of Sca-1 expression, as well as induction of PECAM-1 and Flk-1 expression during ES cell differentiation (Fig. 1C), which is in agreement with other published reports [30].…”
Section: Resultssupporting
confidence: 93%
“…The chemotaxis assays were performed using 5 µm-pore size and 6.5 mm-diameter Costar Transwells (Corning-Costar, Cambridge, MA), as previously described [30]. Cells were washed twice with Hank's balanced salt solution (HBSS) medium, resuspended in 100 µl medium [Iscove's Modified Dulbecco's Medium (IMDM) plus 0.5% BSA] and placed in the upper chamber of the Transwells.…”
Section: Methodsmentioning
confidence: 99%
“…This view is supported by demonstration that β-arrestin2-null mice evidence enhanced sensitivity to the principal psychoactive phytocannabinoid in marijuana, THC [94]. In contrast, CB2R-selective antagonists/inverse agonists that preferentially activate the β-arrestin2 pathway incite cytoskeletal rearrangements in immune cells [95,96] and in lung airway [97] to modulate chemotaxis and invasion of immune and cancerous cells. Although these studies illustrate the important role of β-arrestin in normal, G-protein-dependent GPCR desensitization mechanisms and do not exemplify β-arrestin-biased signaling per se , the results suggest that the degree of β-arrestin bias in vivo is an important characteristic of potential, CBR-targeted therapeutics.…”
Section: Pharmacotherapeutic Implications Of Biased Signaling At Cbrsmentioning
confidence: 99%
“…The quite specific localization of CB 2 , as well as the fact that CB 2 knock-out mice fail to respond to the immunomodulatory effects of classical cannabinoids (Buckley et al, 2000), suggest that CB 2 receptor ligands would have potential therapeutic applications as immunomodulators for the treatment of inflammation and allergy. Several papers report the role of the CB 2 receptor in modulating leukocyte migration (Franklin and Stella, 2003; Jorda et al, 2002; Kishimoto et al, 2003; Massi et al, 2000), activation (Kishimoto et al, 2004), and antigen processing (McCoy et al, 1999). Additional applications could arise from studies on bone physiology, as blockage of CB 2 has been reported to protect from bone loss in ovariectomized mice (Idris et al, 2005).…”
Section: Cannabinoid Receptors: Ligands and Signallingmentioning
confidence: 99%